Lee, Chas., Ranch and Residence, 4 miles west Of San Luis Obispo; Hill, J. C., Dairy Ranch, on the County Road From Cambria to San Luis Obispo, San Luis Obispo County [On Same Plate] (1883)
Hand-tinted lithographs.